PARAMETRIC PRINCIPLES OF TRANSPORT SERVICE QUALITY - Валько, А. М. (Science-based technologies, 2013)
Conceptual approach to operation of transportation enterprises following the principles of quality management is analyzed. Components of service quality as a product of the enterprise activity are identified. The main approaches to the indicators of evaluating the transportation service quality are considered. The problems of formulating the indicators of service management in the transportation and technological sphere are defined. The main parametric principles of transport service quality are outlined. The focus is placed on unconditional and mandatory correspondence to the quality of transport service in accord with the standards, normative requirements and international agreements.